Entrepreneurship in the era of society 5.0: Navigating digitalization for innovation and growth - Putra, Juniawan Mandala; Karundeng, Deby R.; Gofur, Abdul; Tresnadjaja, Reynaldi; Suhara, Ade; Sukmayadi, Sukmayadi; Sopyan, Ahmad (Goodwood Publishing, 2024)
Purpose: This study explores the symbiotic relationship between entrepreneurship and digitalization in Society 5.0, emphasizing the pivotal role of entrepreneurs in navigating and leveraging digital technologies to foster innovation and propel economic development. Research Methodology: This study uses quantitative methods to explore entrepreneurship in the era of Society 5.0, focusing on digitalization for innovation and growth. The population comprises entrepreneurs in Indonesia who use digital technology in their business. The sample comprised of 200 purposively selected entrepreneurs. Data were collected using an online questionnaire on the use of digital technology, innovation, and business growth. Data analysis, including validation, descriptive analysis, and SEM-PLS, was conducted using Smart PLS. The results are expected to provide insights into digital strategies for business innovation and growth. Results: The results highlight how entrepreneurs can leverage digital technologies, such as AI, IoT, and big data, to develop innovative products, improve operational efficiency, expand markets, and make better decisions. The benefits include global market access, improved customer experience, and better business sustainability. This makes entrepreneurs more competitive and responsive to market change. Limitations: Today's entrepreneurship faces limitations, such as technology dependence, adaptation difficulties, data security risks, and the digital divide. Entrepreneurs also encounter global competition, changing regulations, a lack of digital skills, poor technology infrastructure, and funding difficulties. Overcoming these challenges requires support from the government, the private sector, and educational institutions. Contributions: This research helps institutions develop digital policies and training programs, adds to the global literature on entrepreneurship in the Society 5.0, provides digital strategies for management, and improves entrepreneurs' competencies in utilizing digital technologies. It provides practical guidance to support business innovation and growth in the digital age.